2021
DOI: 10.1111/1440-1681.13528
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of cancer stem cell senescence: Current understanding and future perspectives

Abstract: Cancer stem cells (CSCs) are a small population of heterogeneous tumor cells with the capacity of self‐renewal and aberrant differentiation for immortality and divergent lineages of cancer cells. In contrast to bulky tumor cells, CSCs remain less differentiated and resistant to therapy even when targeted with tissue‐specific antigenic markers. This makes CSCs responsible for not only tumor initiation, development, but also tumor recurrence. Emerging evidence suggests that CSCs can undergo cell senescence, a no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 255 publications
(268 reference statements)
0
15
0
Order By: Relevance
“…Senescence is another common characteristic of PoMiCs and TiSCs. It is a mechanism by which TiSCs stop their cell cycle to provide efficient resistance against radiotherapy and anticancer agents [141]. It has been demonstrated that senescence in cancer cells is conducted by mitochondria.…”
Section: Both Postmitotic Ciliary Cells and Tumor-initiating Stem Cel...mentioning
confidence: 99%
“…Senescence is another common characteristic of PoMiCs and TiSCs. It is a mechanism by which TiSCs stop their cell cycle to provide efficient resistance against radiotherapy and anticancer agents [141]. It has been demonstrated that senescence in cancer cells is conducted by mitochondria.…”
Section: Both Postmitotic Ciliary Cells and Tumor-initiating Stem Cel...mentioning
confidence: 99%
“…It is well‐known that crucial signaling components of senescence pathways, such as p16 INK4a , p21 cip1 , and p53, are also critical regulators of cancer stem‐cell‐like phenotypes [118]. A gain of stemness in cancer cells has profound effects on tumour progression and aggressiveness [119].…”
Section: Other Potential Strategies For Treating Senescence‐associate...mentioning
confidence: 99%
“…However, the ability to re-establish the tumour diversity in an experimental animal model should not be equated with the capacity to induce the malignant tumour in the patient. Indeed, four possible sources of CSCs are proposed, including normal stem cells, mature cells, cancer cells and fusion cells [ 13 , 14 ]. Currently, cancer stem cells are considered a state rather than an entity [ 13 , 15 ], likely being in dynamic balance with the general malignant population.…”
Section: Introductionmentioning
confidence: 99%